The Effect of Rotation Speed on the Quality of Friction Welding Joints in Aluminum and Copper - Santoso, Habibi; Surahto, Aep; Ekawati, Fatimah Dian (Fakultas Teknik Universitas Pancasila, 2024)
Welding of two different materials has high difficulty. It will cause porosity and hot cracks. To improve this, a friction welding (FRW) process has been developed to weld materials in a molten state. In this process, the material will be clamped so as not to be thrown, one other material will be rotated and brought together with the other clamped material and the pressure that causes the two sides of the material to meet. The purpose of this study is to determine the strength of welded joints of various materials through tensile testing and microstructure testing in friction welding (FRW) welding. This study used 6061 aluminium and ASTM B187 copper for welding. The cylinder had a diameter of 16 millimetres and a length of 70 millimetres, and the spindle rotational speeds were 1200 rpm, 1400 rpm and 1800 rpm. Welding results were assessed by measuring the strength of weld joints between different types of materials. Test results on welding with different spindle rotational speeds showed that friction welding with 1800 rpm was stronger with a maximum tensile strength of 2762.8 N and a tensile strength of 13.7N/mm2 when compared to 1200 rpm and 1400 rpm. In testing the microstructure of different types of materials, it can be seen that the mixture of the two metals at a rotational speed of 1800 rpm is more melting, so that the unification of the joining of the two materials is better when compared to the rotational speed of 1200 rpm and 1400 rpm.